2019
DOI: 10.1186/s13104-019-4398-6
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions experienced by out-patients taking chlorpromazine or haloperidol at Zomba Mental Hospital, Malawi

Abstract: Objective Drugs for managing mental disorders can cause adverse drug reactions (ADRs) that have negative impacts on patients yet, in Malawi, epidemiological data on the drug-related problems are limited. This study assessed the prevalence and severity of ADRs in out-patients at Zomba Mental Hospital. Results Twenty-six of forty patients (65.0%) were taking haloperidol and 14 (35.0%) chlorpromazine. The commonest diagnosis was schizophrenia (n = 23, 57.5%) followed by ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…While the prevailing perspective suggests that TAPs are less likely to induce metabolic abnormalities compared to AAPs, our research, along with findings from other research groups [ 33 , 34 ], have demonstrated metabolic dysfunction induced by TAPs. In a cohort of SZ patients receiving CPZ monotherapy for over a decade, the prevalence of metabolic syndromes was found to be 31% [ 35 ].…”
Section: Discussioncontrasting
confidence: 39%
“…While the prevailing perspective suggests that TAPs are less likely to induce metabolic abnormalities compared to AAPs, our research, along with findings from other research groups [ 33 , 34 ], have demonstrated metabolic dysfunction induced by TAPs. In a cohort of SZ patients receiving CPZ monotherapy for over a decade, the prevalence of metabolic syndromes was found to be 31% [ 35 ].…”
Section: Discussioncontrasting
confidence: 39%
“…Drugs used to treat neoplasms generally have a high prevalence of ADRs. The prevalence of ADRs is also known to be highly associated with medications for mental and behavioral disorders; at least one adverse drug event has been reported in all patients treated with haloperidol and chlorpromazine 29 . For patients with neoplasms or mental and behavioral disorders, careful attention to the signs of ADRs may prevent their development.…”
Section: Discussionmentioning
confidence: 99%
“…While the prevailing perspective suggests that TAPs are less likely to induce metabolic abnormalities compared to AAPs, our research, along with findings from other groups [33,34],…”
Section: Discussionmentioning
confidence: 45%